Sediment Transport Rate Estimation in Pozm Fishery Harbor by Numerical Modelling and Empirical Formulas (Journal of Civil Engineering Researchers, 2021)
Estimating the amount of alongshore sediment transport (LSTR) is an extremely important task for coastal engineers andcoastal project managers to determine the probability of erosion and sedimentation in shores and ports. There are two popularempirical formulas, CERC and Kamphuis, that can be used to calculate the potential of the LSTR rate of the coast. In thisstudy, sediment transport rate was calculated through experimental formulas and effective simulation in the Pozm Harbor islocated in Oman Sea in the coordination of 25 ° 21 ° N and 60 ° 17 ° E. Using wave data and Specification of sediment. Also,the numerical simulation of this rate is calculated using numerical modeling. The numerical simulation results behind thegroin have been compared with the new hydrography of data was collected in 2017. Furthermore, numerical model has beenevaluated and general morphology has been identified. Based on sediment transport volumes calculated at Pozm harbor, asuitable sediment transport rate can be achieved using this numerical model and the Kamphuis formula.
Keywords: Alongshore Sediment Transport; CERC; Kamphuis; Gulf of Pozm